The atheist bus campaign : global manifestations and responses - Tomlins, Steven. (International Studies in Religion and Society, 2016)
The international "Atheist Bus Campaign" generated news coverage and controversy, and this volume is the first to systematically and thoroughly explore and analyze each manifestation of that campaign. It includes a chapter for each of the countries which enacted - or attempted to enact - localized versions of the original United Kingdom campaign which ran the slogan, "There's Probably No God. Now Stop Worrying and Enjoy Your Life," prominently on public buses. Its novel focus, using a singular micro-level event as a prism for analysis, allows for cross-country comparison of legal and social reactions to each campaign, as well as an understanding of issues pertaining to the historical and contemporary status of religion and the regulation of nonreligion in various national settings.